Chronic Dissection of the Left Subclavian Artery with Pseudocoarctation - Guhathakurta, Soma (2003)
Surgical management of a dissection of the subclavian artery is sparsely reported in the literature because of its rare occurrence. Recently, we treated a patient who had presented with a huge left subclavian artery dissection, a small right subclavian artery aneurysm with pseudocoarctation of the aorta, and a small perimembranous ventricular septal defect. Surgical management of the left subclavian artery dissection and correction of the pseudocoarctation of the aorta were achieved effectively. That unusual combination of pathologic conditions prompted us to report this case. (Tex Heart Inst J 2003;30:221–4)